EXPLORING INTERNATIONAL STUDENTS' MOTIVATION FOR LEARNING DURING THEIR UNIVERSITY STUDIES - I. Angelova (Trakia Journal of Sciences, 2024)
This article examines students' attitudes towards their future profession, which is a key factor in achieving the ultimate learning goals. The aim is to explore students' motivation which influences the formation of their personal and professional orientation. The work uses the methodology “Motivation for university study” proposed by T. Ilinoi, including three scales: “Acquisition of knowledge”; “Mastering a profession”; “Receiving a diploma”. The prevalence of motives in the first two scales indicates adequate choice of profession by the student and satisfaction with it. This paper offers the results of a study on the motivation of international first and second year medical students studying in English. The conclusions show that the motives in the first two scales (“Acquisition of knowledge” and “Mastering a profession”) are predominant in these students, which indicates adequate choice of the profession “medical doctor” by the students.